Unanticipated Political Events and Stock Returns: An Event Study - Dangol, Jeetendra (NRB Economic Review, 2008)
The study focuses on market reaction to announcements of new unanticipated political events using the event analysis methodology. The findings of the study provide a consistent conclusion regarding the existence of information content hypothesis in the Nepalese stock market. The study reveals that good-news (badnews) political announcements generate positive (negative) abnormal returns in the post-event period. The data present important evidence on the speed of adjustment of stock prices to new political information, i.e., in as many as 2 to 3 days from the announcement date. Thus, this paper finds that the Nepalese stock market is inefficient at a semi-strong level, but there is a strong linkage between political uncertainty and common stock returns.